2017
DOI: 10.1111/imm.12749
|View full text |Cite
|
Sign up to set email alerts
|

KLRG1 impairs regulatory T‐cell competitive fitness in the gut

Abstract: Immune homeostasis requires the tight, tissue-specific control of the different CD4 Foxp3 regulatory T (Treg) cell populations. The cadherin-binding inhibitory receptor killer cell lectin-like receptor G1 (KLRG1) is expressed by a subpopulation of Treg cells with GATA3 effector phenotype. Although such Treg cells are important for the immune balance, especially in the gut, the role of KLRG1 in Treg cells has not been assessed. Using KLRG1 knockout mice, we found that KLRG1 deficiency does not affect Treg cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Our results are in concordance with observations in other models, where the lack of KLRG1 expression on T-cells conferred them a functional competitive advantage, because the KLRG1 ligation decreases the TCR signalling, inhibiting the proliferative capacity and decreasing cytokine production. 21 22 We hypothesised that the high production of cytokines, like IL-6 and IFN-γ, and proliferative ability of CD4+T cells in ILA subjects might be independent of their differentiation status (naïve vs memory). However, probably it is a result of the lack of KLRG1 expression, which is a ‘brake-molecule’.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in concordance with observations in other models, where the lack of KLRG1 expression on T-cells conferred them a functional competitive advantage, because the KLRG1 ligation decreases the TCR signalling, inhibiting the proliferative capacity and decreasing cytokine production. 21 22 We hypothesised that the high production of cytokines, like IL-6 and IFN-γ, and proliferative ability of CD4+T cells in ILA subjects might be independent of their differentiation status (naïve vs memory). However, probably it is a result of the lack of KLRG1 expression, which is a ‘brake-molecule’.…”
Section: Discussionmentioning
confidence: 99%
“…ILT3 was described to inhibit the suppressive activity of Tregs (25). The expression of the inhibitory receptor KLRG1 was slightly increased on intestinal Tregs of DDC mice as compared with controls and has been recently shown to inhibit Treg competitive fitness in the gut (36). High expression of KLRG1 on Tregs was also shown to have a negative impact on proliferation as well as stability of Foxp3 expression, and KLRG1 + Tregs were more prone to apoptosis than KLRG1 2 Treg subsets in a NOD mouse model of type 1 diabetes (37).…”
Section: Discussionmentioning
confidence: 99%
“…KLRG1 is an inhibitory receptor expressed by Tregs, but in contrast to the inhibitory receptor CTLA-4, not every Treg has expression, and its expression is only found in a subset of effector-like Tregs. Studies have shown that Tregs lacking in KLRG1 have the advantage of accumulating in the colon but not in the lymphoid organs, indicating that KLRG1 restricts the accumulation of intestinal Tregs, and KLRG1 plays an inherent role in colonic Treg homeostasis, but it does not change the total number of Tregs [46].…”
Section: Regulatory Molecules Of Colonic Treg Production Andmentioning
confidence: 99%